THE CONTRIBUTION OF LONG-RANGE TRANSPORT OF AIR POLLUTION TO THE SULPHUR BUDGET OF THE UNITED ARAB EMIRATES - Evans, Mary Yvonne (My University, 2006)
An air chemistry study over the United Arab Emirates revealed a high concentration of sulphur dioxide. SO2 and its resultant aerosols can have a significant effect on the atmospheric processes. These aerosols could both directly and indirectly affect the climate by scattering solar radiation and increasing the albedo of the atmosphere or by altering the cloud formation processes and characteristics. Sulphur dioxide and the resultant aerosols also have a damaging effect on the environment and on human health. Previous studies reviewed suggest that pollution can be transported for hundreds of kilometres from the source of the emission and affect the air chemistry of the receptor regions. The possibility that long-range transport of pollution to the UAE may have contributed to these high concentrations was also investigated. The possibility that the UAE is a receptor region of pollution transported over long distances is investigated with the intention of identifying the possible source regions of this pollution. In order to examine the import of pollution to the UAE it was important to analyse the background sulphur concentrations of the atmosphere over the UAE.
Student Number :8701745W - MSc research report - Faculty of Science
Keywords: sulphur dioxide; United Arab Emirates; SO2; aerosols; effect on the atmospheric processes; affect the climate; pollution; UAE